Low-res stutters and the slideshow effect: novelistic remediation of digital video conferencing in Rétine by Théo Casciani (Colloquia Comparativa Litterarum, 2025)
The paper aims to put forward a reading of a sub-chapter-long episode in Théo Casciani’s novel Rétine (2019), dedicated entirely to relating a prolonged video call between two characters (of which one is the narrator). Drawing solely on the exemplary scenes from the cited case study, the paper offers a methodological examination of the novelistic text under the angle of poetic representation (or remediation) of digital media and, more specifically, of the contemporary means of teleconferencing. Through a combination of textual analysis and theoretical reflection, the paper sets out to demonstrate that literary intermediality is distinguished by its capacity to engage bilaterally with both mediums getting put into contact, novelistic writing thereby being brought to mobilise unconventional poetical resources, while resorting to procedures of synchronisation between the representing and the represented media that are hardly reducible to the non-poetic uses of language outside of the context of intermedial dialogue established vicariously on the territory of fiction (i.e. by proxy of representation).
Keywords: poetics; novelistic writing; intermediality; Casciani; remediation; digital media; slideshow